Proposta de modelo para avaliação de espaços para pedestres quanto à percepção de seguridade - Silva, Otavio Henrique da (2022)
Different variables may or may not encourage the option of walking as a mode of transport. In particular, several studies have demonstrated the relevance of aspects related to personal safety, especially from a subjective point of view. But, unlike other dimensions related to walkability, perceived safety has not received, so far, a broad and detailed approach to its evaluation. From the perspective of urban planning, the availability of a tool with these characteristics could help formulate more efficient strategies to make cities safer. In this context, this research aimed to build a model for evaluating pedestrian spaces regarding the perception of personal safety, using a multi-criteria approach. For this, three main methodological steps related to (1) construction, (2) development of the technical evaluation system, and (3) the application of the model, named Perceived Personal Safety Index (PPSI), were performed. Regarding the construction of the tool, 17 characteristics of perceived safety that influence the option for walking transport were defined, based on literature, considering the urban dynamics of Brazilian cities. These characteristics were divided into two dimensions (Physical Space and Social Environment). After this, 405 questionnaires were applied to identify the users' understanding of the relevance of the selected characteristics. From the answers obtained, using Exploratory Factor Analysis, a hierarchical structure for the Index in indicators (relating to selected characteristics), factors, and domains (Physical Space and Social Environment), was developed and the relative weights of these three components were determined, using a bottom-up approach. Then, using a weighted linear combination, these indicators, factors, and domains were aggregated. The result of this mathematical expression, variable from 0.0 to 1.0, is equivalent to the final value of the model and indicates the perceived safety condition in a pedestrian space, which can vary from very poor to very good, respectively. The construction of the evaluation system included the definition of technical criteria and procedures, applicable even from images, for each indicator. Fuzzy functions were built to normalize the values of eight indicators within a range of 0.0 to 1.0. For the construction of the curves, information gathered from a panel composed of 36 specialists working in the transport area was used. Once the model was built and the evaluation system defined, the tool received an application. Using the Index, 24 images of the photography and Street View types, representative of different levels of perceived security, were evaluated. Also, six other urban scenarios were evaluated, represented in photographs during the day and night, which allowed exploring the variation of perceived security in these spaces in different situations. In general, the application of PPSI proved to be practical, indicating relevant information about the evaluated spaces from the point of view of personal safety. There is an understanding that the developed Index can be a tool to support decision-making aiming to promote safer spaces for pedestrians. Urban planners and managers and researchers can explore the potentiality of the model and investigate possibilities for adaptations, allowing for its continuous improvement.